2020
DOI: 10.1021/acsnano.0c05454
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Spin Properties in Undoped and Mn-Doped CdSe/CdS-Seeded Nanorods by Optically Detected Magnetic Resonance

Abstract: Controlling the spin degrees of freedom of photogenerated species in semiconductor nanostructures via magnetic doping is an emerging scientific field that may play an important role in the development of new spinbased technologies. The current work explores spin properties in colloidal CdSe/ CdS:Mn seeded-nanorod structures doped with a dilute concentration of Mn 2+ ions across the rods. The spin properties were determined using continuous-wave optically detected magnetic resonance (ODMR) spectroscopy recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 81 publications
1
15
0
2
Order By: Relevance
“…28 Xia et al 45 most recently explored the luminescence of single wurtzite CuInS 2 /ZnS core/shell CQDs in the 4−300 K temperature range. This work uncovered the occurrence of two different events: a band-edge exciton, appearing as a relatively sharp band (in agreement with the assignment given in ref 41), and a second broad emission band at lower energies, emanating from the strong electron−phonon interaction induced by the hole self-trapping, which was reduced with To date, this issue was not addressed using optically detected magnetic resonance (ODMR), which facilitates the determination of the surrounding environments of electrons and holes and their g factors and evaluates the associated spin relaxation times, 49 thus enabling an in-depth understanding of the electronic and spin properties of semiconductors and nanomaterials. 50 Here, we investigate the excited-state electronic structures of luminescent copper-doped and copper-based CQDs using ODMR spectroscopy.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…28 Xia et al 45 most recently explored the luminescence of single wurtzite CuInS 2 /ZnS core/shell CQDs in the 4−300 K temperature range. This work uncovered the occurrence of two different events: a band-edge exciton, appearing as a relatively sharp band (in agreement with the assignment given in ref 41), and a second broad emission band at lower energies, emanating from the strong electron−phonon interaction induced by the hole self-trapping, which was reduced with To date, this issue was not addressed using optically detected magnetic resonance (ODMR), which facilitates the determination of the surrounding environments of electrons and holes and their g factors and evaluates the associated spin relaxation times, 49 thus enabling an in-depth understanding of the electronic and spin properties of semiconductors and nanomaterials. 50 Here, we investigate the excited-state electronic structures of luminescent copper-doped and copper-based CQDs using ODMR spectroscopy.…”
supporting
confidence: 71%
“…The literature survey above highlights a suite of ambiguities regarding the PL mechanism of both Cu-doped and Cu-based CQDs. To date, this issue was not addressed using optically detected magnetic resonance (ODMR), which facilitates the determination of the surrounding environments of electrons and holes and their g factors and evaluates the associated spin relaxation times, thus enabling an in-depth understanding of the electronic and spin properties of semiconductors and nanomaterials …”
mentioning
confidence: 99%
“…Recently, transition metal-doped semiconductor NCs with optical properties have attracted enormous interest. The optical, electrical, and magnetic properties of the host can be dramatically modified owing to the introduction of an additional exciton depletion path by the dopants. Among the various doped NCs, Mn-doped NCs possess long fluorescence lifetimes on the millisecond time scale, large Stokes shifts, and high thermal stability, which will be promising in various applications ranging from optoelectronics to biological science. As a result, various Mn-doped NCs were developed, including Mn-doped CdS, CdSe, and lead–halide perovskites. Although Mn-doped InP-based NCs have the potential to replace doped Cd- and Pb-based NCs, the investigation of their spectroscopic behavior lags far behind those of Cd- and Pb-based NCs. In particular, understanding their fundamental photophysical properties, including the low-temperature exciton behavior, dopant–exciton coupling effect, and multiphoton absorption properties, is a topic worthy of extensive study but is still untouched.…”
Section: Introductionmentioning
confidence: 99%
“…Also the spin-lattice relaxation (SLR) dynamics of the Mn spin system can be measured via time-resolved PL detection after pulsed microwave excitation. Very recently, ODMR studies of DMS CdSe/(Cd,Mn)S core/shell nanoplatelets 20,22 and nanorods 23 have been reported. The measured dynamics of the ODMR signals has been related to the spin-lattice relaxation dynamics of the Mn 2+ spin system and it has been suggested for evaluation of the Mn concentration.…”
Section: Introductionmentioning
confidence: 99%